If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T + -15 = 76 Reorder the terms: -15 + T = 76 Solving -15 + T = 76 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + T = 76 + 15 Combine like terms: -15 + 15 = 0 0 + T = 76 + 15 T = 76 + 15 Combine like terms: 76 + 15 = 91 T = 91 Simplifying T = 91
| 6y+-15=9 | | 7=-7-(p-8) | | 8x+0.5=7x+2 | | 2m+13=25 | | 19m+9n=16 | | 2x+4=4x+16 | | 5x+12=-42-4x | | 9=q-4 | | 5(f-9)=-45 | | n/3-6=10 | | 4x+5=-2+2 | | 9=a-4 | | 8(s-6)=-100 | | y/-23 | | 2(x^2+4)=0 | | 2P(A)=P(B)=5/13 | | 64p=16 | | A=3(a*a)*5a+7(a*a)*2a+7 | | 2P(A)=5/13 | | -10-3x-5x=-42 | | 70=5(4i+2) | | T+32=420 | | 2*n-(n-7)=12 | | 3(t+2)=-9 | | 0.602=j-4.75 | | 3x+2(x+1)=2x+12 | | -6x+10+2x=.22 | | 4ix=6i | | 5x-2y-9z=13 | | 7k-35=24-3k | | 3Z/7-3=-2 | | 49*3-3*(12)= |